Estimating the Returns to Insider Trading: A Performance-Evaluation Perspective - Jeng, Leslie A.; Metrick, Andrew; Zeckhauser, Richard (The Review of Economics and Statistics, 2003)
This paper uses performance-evaluation methodology to estimate the returns earned by insiders when they trade their company's stock. Our methods are designed to estimate the returns earned by insiders themselves and thereby differ from the previous insider-trading literature, which focuses on the informativeness of insider trades for other investors. We find that insider purchases earn abnormal returns of more than 6% per year, and insider sales do not earn significant abnormal returns. We compute that the expected costs of insider trading to noninsiders are about 10 cents for a $10,000 transaction.